PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN MATEMATIKA KELAS IV SD NEGERI 9 TA KECAMATAN TANETE RIATTANG KABUPATEN BONE - Firdaus; Kadir, Abd; Putri Faisal, Sri Afriani (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study was motivated by the application of the Discovery Learning model to improve students' critical thinking skills in learning mathematics class IV SD Negeri 9 TA Tanete Riattang District, Bone Regency. The objectives of the study were 1) to describe teacher activities in the application of the Discovery Learning model in learning mathematics in class IV SD Negeri 9 TA Tanete Riattang District, Bone Regency. 2) to describe students' activities in the application of the Discovery Learning model in learning mathematics in class IV of SD Negeri 9 TA Tanete Riattang District, Bone Regency. 3) to determine the improvement of students' critical thinking skills in learning mathematics in class IV SD Negeri 9 TA through the application of the Discovery Learning model. The approach used in this research is descriptive qualitative. The subjects in this study were all fourth grade students totaling 28 people and the fourth grade homeroom teacher. The data collection techniques used were observation, tests, and documentation. Data analysis techniques by reducing data, presenting data, and drawing conclusions. Based on the results of the research that has been carried out, students' critical thinking skills have increased through the Discovery Learning learning model. This can be seen from the results of the first cycle test reaching the moderately critical category and in cycle II reaching the critical category. It can be concluded that the Discovery Learning model can improve students' critical thinking skills in learning mathematics.